A participação dos telespectadores na televisão : uma análise do telejornal Bom Dia São Paulo - Silva, Alexandra Freitas da (2020)
This dissertation investigates the public's participation in Rede Globo's Bom Dia São Paulo newscast. The chosen object has been on the air since 1977 and is the station's oldest local / regional program. During these 43 years, the relationship with its audience has undergone adaptations. Through the analysis of five editions, the types of participation are established, which present a distinction between themselves and in the way they cause changes in the news. The survey took into account the format and messages sent by viewers. The methodological proposal used was Content Analysis by Laurence Bardin (2004), which made it possible for the news to be observed through two categories: participation and interactivity. Thus, it was possible to identify six types of participation, formats and the contents that change the reports. It was concluded that the public has space and that it also interferes in the content of the news. In the theoretical framework, authors such as Wolton (1996, 2011), Scolari (2014), Jenkins (2009), Canitto (2010), Vizeu (2008,2009 Carlón (2014), Becker (2015), Finger were used, among others (2011), Fechine (2014), Tourinho (2010).